Review of Pharmacological Activities of Vetiveria zizanoide (Linn) Nash - Saroosh Zahoor; Sammia Shahid; Urooj Fatima (Journal of Basic & Applied Sciences, 2018)
Vetiveria zizanioides (Linn) Nash is a perennial magical grass of family poaceae commonly known as Khas which is highly valued grass due to its adventitious root system. It is widely distributed in the Pakistan. It is cultivated in all provinces of Pakistan due to its great economic importance. This grass grows plain ascending up to 1200m. Mostly roots stem and leaves were used for treatment of different diseases by ancestors. Adventitious roots contain essential oil which used for multipurpose such as perfumery and in pharmacological industry. Vetiver oil contains approximately 150 compounds, including sesquiterpenoide, hydrocarbons. Phytochemical analysis of leaves shows the presence of flavonoides, saponins, tannins and phenols. Various tribes of India used this tuft grass for commercial purposes. Khas serve as broom, for cooling, roof of huts and as medicine for different diseases such as sunstroke, ulcer, fever, epilepsy and in skin diseases. In this study we summaries the magical pharmacological activities of Vetiveria zizanioides such as anti inflammatory, antibacterial, antifungal, and anti malarial, anti tubercular, anti hyperglycemic, anti hepatoprotective and antioxidant activity.